Test–retest reliability of rapid whole body and compartmental fat volume quantification on a widebore 3T MR system in normal‐weight, overweight, and obese subjects. Issue 6 (1st June 2016) - Newman, David; Kelly‐Morland, Christian; Leinhard, Olof Dahlqvist; Kasmai, Bahman; Greenwood, Richard; Malcolm, Paul N.; Romu, Thobias; Borga, Magnus; Toms, Andoni P.
Abstract : Purpose: To measure the test–retest reliability of rapid (<15 min) whole body and visceral fat volume quantification in normal and obese subjects on a widebore 3T MR system and compare it with conventional manual segmentation. Materials and Methods: Thirty participants (body mass index [BMI] 20.1–48.6 kg/m 2 ) underwent two whole‐body magnetic resonance imaging (MRI) examinations on a widebore 3T machine using a 2‐point Dixon technique. Phase sensitive reconstruction and intensity inhomogeneity correction produced quantitative datasets of total adipose tissue (TAT), abdominal subcutaneous adipose tissue (ASAT), and visceral adipose tissue (VAT). The quantification was performed automatically using nonrigid atlas‐based segmentation and compared with manual segmentation (SliceOmatic). Results: The mean TAT was 31.74 L with a coefficient of variation (CV) of 0.79% and a coefficient of repeatability (CR) of 0.49 L. The ASAT was 7.92 L with a CV of 2.98% and a CR of 0.46 L. There was no significant difference in the semiautomated and manually segmented VAT ( P = 0.73) but there were differences in the reliability of the two techniques. The mean semiautomated VAT was 2.56 L, CV 1.8%, and CR 0.09 L compared to the mean manually segmented VAT of 3.12 L, where the CV was 6.3% and the CR was 0.39 L. Conclusion: Rapid semiautomated whole body and compartmental fat volume quantification can be derived from a widebore 3T system, for a range of body sizes including obese patients, with "almost perfect" test–retest reliability. J. Magn. Reson. Imaging 2016;44:1464–1473.